Pengaruh Lingkungan Keluarga terhadap Intensitas Belajar Siswa Kelas XII SMA Negeri 4 Samarinda - Maulana, Farhan; Abu, Ilham; Astuti, Ratna Fitri (Educational Studies: Conference Series, 2024)
The research in this thesis is motivated by the family environment that influences the intensity of student learning. Therefore, the focus of the research in this thesis is how the family environment affects the intensity of learning. This study is to determine the influence of the family environment on the intensity of learning of class XII students of SMA Negeri 4 Samarinda. The type of research conducted is descriptive quantitative research. The informants in this study were class XII. Data collection was carried out by direct observation and questionnaires of class XII students. Based on the results of the study, it showed that 43.3% of students were very supported by their families in the student learning process, then 32.7% of students were sufficiently supported by their families, but there were 22% of students who received less support for learning from their family environment, and there were 2% of students who did not receive support from their family environment.